Bibliography on Cold Regions Science and Technology. Volume XXIV, Part 2. Index. - COLD REGIONS RESEARCH AND ENGINEERING LAB HANOVER N H (1970)
The publication is a bibliography of research sponsored by the Cold Regions Research and Engineering Laboratory with author and subject indexes included. See also Volume 23 Index, AD-696 403, and Volume 24, AD-715 769.